Effects of Dietary Supplementation with Graded Levels of Maca (Lepidium meyenii) on Nutrient Intake of Local Goat Does and Growth Performance of Their Kids (Indian Journal of Animal Production and Management, 2025)
This study evaluated the effects of dietary supplementation with graded levels of maca (Lepidium meyenii) root powder on nutrient intake of Iraqi local Black goat does and on growth performance of their offspring before and after weaning. The experiment was initiated at the beginning of the third month of gestation and continued until six months post-weaning. Twenty does (2–3 years old; 41.32 ± 2.11 kg) were randomly assigned to four treatments (n = 5), while sixteen post-weaning male kids (3 months old; 14.81 ± 2.43 kg) were allocated to four corresponding groups (n = 4). Animals received maca supplementation at 0, 2, 4, or 6 g/animal/day in addition to a basal diet formulated to meet nutritional requirements. Daily feed intake and concentrate refusals were recorded throughout the experimental period. Results showed that roughage intake of does was significantly increased in the supplemented treatments compared with the control. Offspring born to does receiving the highest level of maca exhibited greater body length at birth, while chest circumference at weaning was improved in the moderate supplementation groups. Post-weaning performance of male kids indicated a significant increase in final body weight, with the highest value observed in the 2 g/day treatment, followed by the 6 g/day treatment. Furthermore, total feed intake and its components were positively influenced by maca supplementation. In conclusion, dietary supplementation with maca root powder, particularly at 2 and 6 g/animal/day, enhanced feed intake of does and improved growth performance of their kids, suggesting its potential.
Keywords: Maca; Lepidium meyenii; Goat does; Feed intake; Kid growth; Natural feed additive